Service utilization of health facilities after handover to local government study from Kanchanpur district. - Bhatta, Ramesh (2006)
SUMMARY: This study attempts to explore the trends of services utilization form the health facility by the community before and after handover and at the same time the study also comprises the role played by the local bodies and support provided by them for proper management and improving the service. This study aggregates the information form three different dimensions i.e. by reviewing of service statistics of three similar months of the year just before handover and of this year. Similarly perspective of Health Facility Management and Operation Committee (HFMOC) and perspective of Community toward the service provided before and after handover, their trend for service utilization and support contributed by HFMOC for the better management the service. Study is conducted in seven health facilities out of the total health facilities of Kanchanpur district which were handover to local government. From management committees 21 member were included having three members from each committee (Health facility Incharge, VDC Secretary and Dalit/Janjati representative). Similarly 210 respondents from different wards of the respected VDCs were included by using 30 cluster sampling method. As the main purpose of hand over of health facilities to the local bodies is to improve the health services and make it as desired by the community by considering their priority and by mobilization the local resources. The study shows some positive outcome of service utilization by considering the service statistic, which shows that patients visiting health facility have increased by about 16% than that of before handover. The supportive reason behind having the increasing trend of patients in the health facility after handover as mentioned by the management committee members and supported by majority of the community respondents is due to the regular and timely opening of the health facility and regular presence of health worker, regular availability of drugs at cheaper cost, competent health worker with good behavior, proper privacy during patient examination, presence of waiting room and appropriate waiting time in the health facility before taking service, regular and appropriate management of service. involving community in various health related activities and decision making process and by providing encouraging and supportive environment for service utilization to those who are unable to afford the service charge. Management committees have initiated lab service on their own effort and they are also able to hire staff on their own financial resources, which shows that they have been capable for appropriate management of their health facilities. But still there are certain obstacles that the committee is facing i.e. mainly due to the absence of formal elected political body due to which VDC secretary has been taking the responsibility of chairmanship of the committee since VDC secretary are busy with their own job responsibilities so due to the lack of time and unable to stay at VDC because of the security problem, they are not able to smoothly conduct the activities and actively participate in managerial activities. In some of VDCs due to the security problem members have left their VDCs and are staying in Mahendranagar due to which they are unable to participate in the regular meeting and support the committee. Deterioration of security situation has also effect on the regular supervision and monitoring activity of the management committee. In spite of various problems and constrains management committees have shown their best effort for the better management of service. As responded by the committee members and from the review of the statistics it could been seen that the service have been better managed and utilization have increased after handover, but still to be more competent and successful in coming days they need to be frequently monitored and guided by the responsible authorities.